SOSIALISASI KEWIRAUSAHAAN DAN PELATIHAN PEMBUATAN KRIPIK TALAS DI DESA SELAT KECAMATAN NARMADA KABUPATEN LOMBOK BARAT - Mubarak, Yazid Bustami Al; Alawiyah, St. Safira; Reviana, Isabela Putri; Safira, Annisa Nanda; Nurwasilah, Lisda; Maulida, Nurul; Hotimah, Husnul; Gomes, Aprilia Nelina; Isnaini, Lilis Nur; Dasilva, Jennifer Isabelana (Universitas Mataram, 2023)
Community Service Program (KKN) has become part of educational activities as well as community service. The importance of this activity is to become a life lesson in the midst of the community in helping solve the problems faced by the community. Selat Village, Narmada District, West Lombok Regency has abundant potential for plants in the form of taro. The main problem in community service is the lack of potential agricultural products. When taro tubers are abundant, the market doesn't absorb the yield, so this taro has no selling value. This potential can be utilized by the community to increase the added value and selling value of these crops. For this reason, it is necessary to carry out training activities for processing taro tubers into products that are useful and have economic value so that they can increase the income of the people of Selat Village. The purpose of this community service is to provide knowledge to residents who participate in training activities so that they are able to produce or process taro tubers into taro chips that are in demand by consumers and are able to apply marketing in selling products. Service Implementation Method, carried out by counseling, demonstration and practice methods. The result of community service with the entrepreneurship outreach program and training in making taro chips in Selat Village is an increase in taro processing skills and it is hoped that the community will be able to open MSME businesses so that they can improve the community's economy.